Enhancing Students’ Environmental Stewardship Through Teacher-Led Classroom Cleanliness Innovations At Sd Assunniyyah - Firda Maghfirotus S; Ainun Zahro Hidayati; Titin Nurhidayati; Suniati (Al-Hikmah: International Journal of Islamic Studies, 2026)
This study aims to explore teacher innovation in fostering students' love for the school environment through classroom cleanliness programs at SD Assunniyyah Kencong. A clean and comfortable school environment is a crucial element in creating a conducive learning atmosphere while shaping environmental awareness from an early age. This research employs a descriptive qualitative method, with data collected through observation and in-depth interviews. The results indicate that the teacher's role is vital in increasing student awareness through various innovations, such as creative class duty programs, cleanliness competitions, award systems, clean living practices, and the integration of environmental education into the curriculum. These innovations are proven effective in increasing student engagement in maintaining cleanliness and fostering a sense of belonging to the school. Program success is supported by active collaboration between teachers, students, and the school, despite challenges regarding low student awareness and limited facilities. It is concluded that teacher creativity is the determining factor in developing environmentally conscious characters in elementary students. This initiative must be implemented continuously with the support of all school members so that a culture of cleanliness becomes deeply ingrained in the students' character. Well-planned teacher innovation significantly influences the creation of a clean, healthy, and sustainable learning environment for the students' future.